Subchronic feeding study of high-free-lysine transgenic rice in Sprague-Dawley rats. (July 2017) - Yang, Qing-Qing; He, Xiao-Yun; Wu, Hong-Yu; Zhang, Chang-Quan; Zou, Shi-Ying; Lang, Tian-Qi; Sun, Samuel Sai-Ming; Liu, Qiao-Quan
Abstract: Lysine is considered to be the first essential amino acid in rice. An eliteH igh-F ree-L ysine transgenic line HFL1 was previously produced by metabolic engineering to regulate lysine metabolism. In this study, a 90-day toxicology experiment was undertaken to investigate the potential health effect of feeding different doses of HFL1 rice to Sprague-Dawley rats. During the trial, body weight gain, food consumption and food efficiency were recorded, and no adverse effect was observed in rats fed transgenic (T) rice diets compared with non-transgenic (N) or control diets. At both midterm and final assessments, hematological parameters and serum chemistry were measured, and organ weights and histopathology were examined at the end of the trial. There was no diet-related difference in most hematological or serum chemistry parameters or organ weights between rats fed the T diets and those fed the N or control diets. Some parameters were found to differ between T groups and their corresponding N and/or control groups, but no adverse histological effect was observed. Taken together, the data from the current trial demonstrates that high lysine transgenic rice led to no adverse effect in Sprague-Dawley rats given a diet containing up to 70% HFL1 rice in 90 days. Highlights: Subchronic feeding study of different doses of high-free-lysine (HFL) transgenic rice in Sprague-Dawley rats. No diet-related difference in physiological and biochemical parameters between groups fed transgenic rice diets (T) and non-transgenic (N) or control diets. No adverse effect in growing rats given a diet containing up to 70% HFL transgenic rice.